2008
DOI: 10.1364/ol.33.002992
|View full text |Cite
|
Sign up to set email alerts
|

Compression of intense ultrashort laser pulses in a gas-filled planar waveguide

Abstract: We report on the compression of intense ultrashort laser pulses for the purpose of producing few-cycle optical pulses at the multimillijoule level by using a planar waveguide (PWG). The PWG is composed of two parallel glass slabs separated by a gap of 100 microm and mounted in a gas chamber filled with a noble gas. In comparison with the conventional hollow-fiber-based pulse compression technique, the use of a PWG enables the injection of high-energy ultrashort pulses, because the input laser beam is confined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 8 publications
0
28
0
Order By: Relevance
“…It was proposed recently that planar hollow waveguides can allow generation of few cycle pulses with much higher energies [7]. In the first experimental demonstration of this principle Chen et al generated pulses of 12 fs duration with 2 mJ energy [8].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was proposed recently that planar hollow waveguides can allow generation of few cycle pulses with much higher energies [7]. In the first experimental demonstration of this principle Chen et al generated pulses of 12 fs duration with 2 mJ energy [8].…”
mentioning
confidence: 99%
“…Small-scale self focusing causes the amplification of noise in the beam and deterioration of the spatial mode. At sufficiently high input energy the beam can even break into filaments [8]. For nonlinear propagation in a planar waveguide, since any mode other than the fundamental in the guided direction is strongly attenuated, one expects small scale self focusing to act only in the free direction.…”
mentioning
confidence: 99%
“…By use of gas-filled planar hollow waveguides for post-compression, the pulse energy can easily be up-scaled by increasing the beam size in one spatial direction, while keeping the intensity inside the waveguide at levels benefiting efficient self-phase modulation, but limiting ionization. In the first experimental realization it was recognized that modulational instability due to one-dimensional, small-scale selffocusing along the unguided waveguide direction could result in strong deterioration of the transverse beam profile and in the extreme to break-up of the beam into several filaments [20]. Shortly after, some of the authors of this publication showed that by carefully controlling experimental parameters, such as gas pressure and waveguide length, a balance between spectral broadening and beam deterioration can be achieved and demonstrated compressed pulses at the 10 mJ level with good focusability [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…52 Because the input laser beam is confined only in the lateral direction perpendicular to the waveguide plane, thus enlarging the mode area, few cycle pulses with much higher energies can be generated. [8][9][10] In the former scheme spatial beam quality still remains a problem. A summary of the most important laser sources delivering intense few-cycle pulses in the NIR is listed in table 2.1.…”
Section: Filamentationmentioning
confidence: 99%
“…This methods are limited to sub-milijoule level due to material damage or intensity clamping. In order to increase the energy throughput, pressure gradients, 7 planar hollow waveguides 8,9 and tapered waveguides 10 were proposed. Yet, the waveguide still imposes a limit on the aperture and thus the power of the compressed pulse.…”
Section: Introductionmentioning
confidence: 99%